Production of biodiesel from chicken tallow - Kau Juelun (School of Environmental Engineering University Malaysia Perlis, 2011)
Biodiesel, an alternative diesel fuel, is made from renewable biological sources such as vegetable oils and animals fats. In the research, waste chicken tallow is used as the low cost sustainable potential feedstock for biodiesel production. Alkali transesterification or methanolysis is the main process to produce the biodiesel in the research. Effect of amount of catalyst, amount of methanol and reaction time on biodiesel was investigated.